Da subjetividade do homem á materialidade do boi: recriando áfricas na diáspora - Morais, Viviane Lima de (2009)
We started the car, in the Bumba-meu-boi, to understand the universe yet little explored the relationship between man and animal in Brazil. I reviewed the various processes that enabled the man to take ownership of cattle and feed to produce sign and material culture. Redo the path traveled by the first group of cattle arriving in the country, the archipelago of Cape Verde, enter the African continent to unveil the relationship before and during the processes of colonial slavery. I noticed several changes in the interaction between man and nature that resound here, the other side of the Atlantic, recreated in the conflicting areas of the ideology of slavery. In the first pages resuscitated animals that enter the earth, responsible for their territorial and cultural setting, the metaphors and metonymy resignificamos of man enslaved Africans who built with his hands, feet and voice to social and geographical boundaries of the Earth from Santa Cruz